Factors affecting farmers’ decision to convert to organic farming : a case study in Argentine Pampas - Elustondo, Luciana; Cabrini, Silvina María (2020)
Organic foods are perceived as more nutritious, better tasting and more sensitive to the welfare of animals and the environment, compared to conventionally produced foods. It is estimated that the future growth of organic agriculture will depend on supply constraints rather than changes in demand. So far, the trend has reflected that demand grows faster than supply (FAO, 2016). The organic agriculture appears as an alternative of sustainable intensification, of importance of Argentina, with a recent growth, although with very limited diffusion. The area harvested under certification is about 80,000 ha (SENASA, 2018). Organic production has the potential to generate not only on-farm benefits but also offfarm positive effects. Then, it is interesting to understand the incentives and limitations of producers to participate in this type of production, in order to provide information valuable for the design of policies that encourage organic production. This paper aims to identify the factors affecting the decision of producers to convert to organic agriculture and describe the main strengths and limitations of extensive organic agriculture in Argentine main agricultural region, through the case study of the group of organic farmers Pampa Orgánica Norte.